2018
DOI: 10.20429/ijsotl.2018.120216
|View full text |Cite
|
Sign up to set email alerts
|

Leave Them to Their Own Devices: Healthcare Students' Experiences of Using a Range of Mobile Devices for Learning.

Abstract: Given recent advances in mobile technologies, there has been a shift from e-learning to mobile learning in UK universities, yet there are few data about how students select and use mobile devices, and whether e-learning systems and materials are fully compatible.Healthcare students have placements in clinical practice where they use mobile devices to access university course information and learning materials.This study investigated student use of devices in the School of Health Sciences, City University Londo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Studies conducted in other countries in Africa [ 6 18 , 23 – 25 ] corroborate these concerns indicated by the beneficiary students of the e-Learning pilot project. In light of these concerns, dedicating ring-fenced budget for ICT infrastructural development by university management would be an important intervention to improve on the existing infrastructural deficits.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Studies conducted in other countries in Africa [ 6 18 , 23 – 25 ] corroborate these concerns indicated by the beneficiary students of the e-Learning pilot project. In light of these concerns, dedicating ring-fenced budget for ICT infrastructural development by university management would be an important intervention to improve on the existing infrastructural deficits.…”
Section: Discussionmentioning
confidence: 59%
“…Qualitative interviews with some teaching faculty and ICT staff corroborated this conclusion since these stakeholders acknowledged capacity deficits on the Moodle platform in the early days of its deployment. Empirical studies in Ghana [ 4 , 19 ] and other developing countries [ 6 18 , 23 – 25 ] on e-Learning innovations for health trainees have also pointed to similar concerns of limited human resource expertise as an existing challenge to e-Learning programme implementation in Africa and other continents with limited resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, an empirical study by Alhassan et al [ 32 ] among health tutors in selected nursing and midwifery training schools in Ghana found, limited ICT infrastructure is not only a source of frustration to students and tutors but also an important barrier to quality teaching and learning in these training institutions. Similar studies on the use of mobile technology by health trainees [ 33 37 ] and qualified personnel in clinical practice [ 32 , 36 – 41 ] revealed that even though the technology is highly beneficial there are constraints regarding its use especially lack of seamless internet connectivity and adaptation by relatively older cadre of health trainees. Findings of this feasibility and preparedness study offers the opportunity to leverage the high mobile phone penetration rate to improve on the quality of pre-service training for healthcare professionals through mobile and e-learning innovations.…”
Section: Discussionmentioning
confidence: 90%
“…Gamification is a valuable resource for developing autonomy and independence among the students, and its application is increasingly more frequent in scenarios beyond the classroom [15]. The theme of "secret agents" was implemented under the pretext of the analytical program based on the five central competencies of the course, since it was considered that these competencies are characteristics of analytical people who can make decisions and propose strategies according to the environment or situation presented to them (adaptation to change).…”
Section: Analysis Of Resultsmentioning
confidence: 99%